Effect of Aqueous Root Extract of Decalepis hamiltonii on Lopinavir Pharmacokinetics and Midazolam Pharmacodynamics - Sandopa, Dhanunjaya; Vellapandian, Chitra (Indian Journal of Pharmaceutical Education and Research, 2024)
Background: The traditional plant Decalepis hamiltonii, indigenous to southern India, is a key component in the well-known herbal beverage nannari. It has also been utilised as a general vitalizer and paediatric rejuvenator in siddha, ayurveda, and folk medicine. However, it has been demonstrated that this plant's phytoconstituents can modulate CYP450 enzymes, which are crucial for determining the fate of xenobiotics within the body. It has not yet been observed that this plant's modulatory property would result in herb-drug interactions when used in conjunction with xenobiotics. Materials and Methods: The goal of the current investigation was to determine how Decalepis hamiltonii affected the pharmacokinetics of the CYP3A substrate lopinavir and the pharmacodynamics of another CYP3A substrate midazolam, in rats. An in vivo pharmacokinetic study of oral lopinavir (35.50 mg/kg), and the effects of Aqueous Root Extract of Decalepis hamiltonii (AREDH) pretreatment on the pharmacokinetic parameters were evaluated. Further the acute and chronic pretreatment of AREDH on pharmacodynamics of midazolam was assessed through measuring hypnotic responses produced in rats. Results: The findings showed that, in comparison to the control, AREDH pretreatment significantly decreased the area under the concentration-time curve (AUC), while a small but not statistically significant change was seen in the half-life of lopinavir (T1/2 k10), the amount of time needed to reach the peak plasma concentration (Tmax), and the elimination rate constant (k10). In addition, AREDH pretreated groups had significantly less sleep duration than the control group irrespective of the pretreatment duration. However, there was no discernible difference in sleep latency. Conclusion: Conclusively, it suggests that Decalepis hamiltonii caused CYP3A-mediated increased metabolism via inducing the enzyme, which significantly decreased the oral bioavailability of lopinavir. Clinical investigations are necessary to assess this interaction's therapeutic importance in more detail.
Keywords: Decalepis hamiltonii; Herb-drug interactions; Lopinavir; Midazolam; CYP3A; Pharmacokinetics; Pharmacodynamics